2019
DOI: 10.29252/ieepj.1.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Investigating and Comparing the Effectiveness of Cognitive-Behavioral Therapy and Acceptance and Commitment Therapy on Emotional Self-efficacy of Family Headed Women

Abstract: Although emotions are the evolutionary mechanism, it has been attempted to control and direct these evolutionary programs. One of the ways to control emotions is to promote emotional self-efficacy. The purpose of this study was to investigate and compare the effectiveness of CBT and ACT on emotional self-efficacy of the family-headed women. For this purpose, 200 women were selected from among female-headed families under the auspices of the Imam Khomeini Relief Committee (IKRC) of Tehran. They were tested by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In this approach, individuals are encouraged to experience better feelings and behave more appropriately by recognizing their negative thoughts and cognitive distortions, challenging them, and resuming their thoughts. Earlier studies have shown that CBT is effective in anxiety management, depression control, and increased life satisfaction, improving mood and anxiety symptoms, enhancing patience and improving the quality of life of patients, improving relationships with peers, reducing depression, and increasing life satisfaction (MOTAMEDI et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, individuals are encouraged to experience better feelings and behave more appropriately by recognizing their negative thoughts and cognitive distortions, challenging them, and resuming their thoughts. Earlier studies have shown that CBT is effective in anxiety management, depression control, and increased life satisfaction, improving mood and anxiety symptoms, enhancing patience and improving the quality of life of patients, improving relationships with peers, reducing depression, and increasing life satisfaction (MOTAMEDI et al, 2019).…”
Section: Introductionmentioning
confidence: 99%